A review of the current literature on the utility of the Functional Movement Screen as a screening tool to identify athletes' risk for injury - Monaco, J.-T.; Schoenfeld, B. J. (Strength and Conditioning Journal, 2019)
The Functional Movement Screen (FMS) is a popular movement screening tool used by rehabilitation professionals and strength and conditioning specialists, often for the purpose of injury prevention. Although the fms may facilitate the ability for rehab therapists and trainers to determine movement dysfunctions, the ability to predict injury has recently come under scrutiny. The following review examines the current literature on the utility of the fms as a screening tool to identify athletes' risk for injury.